Fabrication of Hydrophobic Lignin-Based Films through Tandem Chemical Modification and Plasma Treatment - JEONG, KIM MIN; Lee, Young A.; Wu, Jie; Kim, Hyeyun; Ko, Ja Kyong; Moon, Myoung-Woon; Yoo, Chang Geun; Jeong, Keunhong; Kim, Kwang Ho (AMER CHEMICAL SOC, 2025)
Fully renewable hydrophobic materials offer a promising solution to addressing environmental challenges. Lignin, a relatively underutilized renewable polymer that naturally exhibits hydrophobicity, shows potential as a blend material in various applications. However, current approaches using technical lignin as a primary component or additive in renewable film manufacturing often rely on nonrenewable, external hydrophobic agents. Here, we developed a tandem strategy to create a fully renewable, hydrophobic lignin-based film. First, lignin was esterified by incorporating long-chain palmitic groups to enhance its hydrophobicity. A poly[(R)-3-hydroxybutyrate] (PHB) film containing 20% palmitoylated lignin demonstrated improved hydrophobicity, with the water contact angle (WCA) increasing from 75.4 to 106.7°. To further enhance hydrophobicity, the film underwent oxygen plasma treatment, which introduced macroscopic surface roughness in the form of “nanoforests.” This treatment significantly increased the WCA to 139°, confirming the effectiveness of the tandem strategy for producing hydrophobic 2D materials. Molecular dynamics simulations revealed that the C16 chain in palmitoylated lignin created a more compact complex with PHB through strong van der Waals interactions and optimized hydrogen bonding, suggesting potential for developing high-lignin-content films. This work demonstrates a facile approach for fabricating fully renewable, hydrophobic composite films without the need for external materials.